A inflação como fenômeno real e monetário: distintas visões a partir da ortodoxia e heterodoxia econômica - PINTO JUNIOR, Erivam de Jesus Rabelo (2017)
The cause and effect relationships between the variations in aggregate demand and inflation are distinct and depend on the theoretical approach adopted for the examination of the inflationary process. Excess demand is not always the prime source of inflation. In some cases, the inflation dynamics can be analyzed from some variables that, when generating cost increases, cause an increase in the general level of prices. The conventional approach admits that equilibrium in the labor market is essentially automatic and that inflation is always a consequence of excess demand. From this diagnosis, he concludes that the role of the monetary authority is to control the demand to a level that corresponds to the non-accelerating unemployment inflation rate, through the manipulation of the interest rate. For the Post-Keynesian approach, this view can only be constructed from the idea that money is endogenous and not neutral, which allows one to see inflation not as a result of excess demand, but that the growth of the currency may have been growth of economic costs. On the other hand, the Distributive Conflict approach seeks to understand the inflationary process from the social and political environment of an economy, considering what are the actions and reactions of the various groups that comprise it and the way in which each group takes initiative in the intention to defend income. The formation of the general level of prices occurs in a different way from those that reflect the scarcity of factors of production and from this analysis, the orthodox elements that associate the inflationary process with anenvironment of excess demand is not present. This research presents a theoretical narrative of how the orthodox approach considers that excess or acceleration of demand is capable of causing inflation and, in the face of such a diagnosis, how it should be combated, followed by interventionist discussion, which adds the endogeneity of money in the analysis of the inflationary process and which considers that inflation can occur even before demand reaches the level of full employment. Subsequently, it seeks to delineate the emergence of Structuralist thought, which opposed dominant theories and sought to understand the inflationary dynamics in Latin American countries from their specificities. Such theorists have provided the basis for the approach that is subsequently analyzed, that of Distributive Conflict. For this, the research tries to expose the real cost variables that are used to analyze the inflationary dynamics of an economy in a given time period, then a comparison of how the approaches exposed diverge and converge in relation to the analysis of inflationary dynamics and the mechanisms which must be adopted in pursuit of the equilibrium of the general level of prices.